(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluate the results of treating closed TLC fractures of the humerus in children by percutaneous closed reduction under fluoroscopy at Nghe An Obstetrics and Pediatrics Hospital. Subjects and methods: Prospective study describing 62 patients with closed TLC fractures of the humerus in children, grade III according to Gartland and treated by percutaneous closed reduction under fluoroscopy at Nghe An Obstetrics and Pediatrics Hospital from January 2022 to June 2023. Results: Average age: 7.21±2.18 (4-15), mainly 7-10 years old (54.84%). Female/male ratio: 1.95/1, all patients underwent closed reduction surgery, no case required open reduction surgery. Secondary displacement after Kirschner penetration was 2 cases. There was 1 case of paraplegia after cross nail penetration and complete recovery after 2 months of follow-up. Clinical results were good in 45 patients, fair in 10 patients (88.71% good and fair), 6 cases had average results and 1 patient had poor results. Conclusion: This technique is very effective and is a safe choice in the treatment of grade III supracondylar humerus fractures in children. This method brings many good results to patients: No open surgery, no blood loss, the fracture is reduced to the correct anatomical position.